2016
DOI: 10.1021/acs.jpca.6b05423
|View full text |Cite
|
Sign up to set email alerts
|

Transient versus Static Electron Spin Relaxation in Mn2+ Complexes Relevant as MRI Contrast Agents

Abstract: The zero-field splitting (ZFS) parameters of the [Mn(EDTA)(H2O)](2-)·2H2O and [Mn(MeNO2A)(H2O)]·2H2O systems were estimated by using DFT and ab initio CASSCF/NEVPT2 calculations (EDTA = 2,2',2″,2‴-(ethane-1,2-diylbis(azanetriyl))tetraacetate; MeNO2A = 2,2'-(7-methyl-1,4,7-triazonane-1,4-diyl)diacetate). Subsequent molecular dynamics calculations performed within the atom-centered density matrix propagation (ADMP) approach provided access to the transient and static ZFS parameters, as well as to the correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 82 publications
5
19
0
Order By: Relevance
“…Under acidic conditions, MnO 2 would be decomposed to Mn 2+ with five unpaired 3d electrons, which was a T1-shortening agent in MR imaging. [44] The MR imaging and corresponding quantification analysis in Figure 6D,E showed that the T1-MR signals enhanced fourfold in the tumor at 24 h post-injection of nanoprobe, verifying the high tumor accumulation of nanoprobe, which was consistent with in vivo FLI results.…”
Section: In Vivo Imaging With Nanoprobe H-mno 2 /Dox/bpqdssupporting
confidence: 80%
“…Under acidic conditions, MnO 2 would be decomposed to Mn 2+ with five unpaired 3d electrons, which was a T1-shortening agent in MR imaging. [44] The MR imaging and corresponding quantification analysis in Figure 6D,E showed that the T1-MR signals enhanced fourfold in the tumor at 24 h post-injection of nanoprobe, verifying the high tumor accumulation of nanoprobe, which was consistent with in vivo FLI results.…”
Section: In Vivo Imaging With Nanoprobe H-mno 2 /Dox/bpqdssupporting
confidence: 80%
“… 81 However, the [Mn(MeNO2A)(H 2 O)] complex, which is closely related to those investigated here, displays a positive D value according to CASSCF/NEVPT2 calculations (+0.045 cm –1 ). 34 These results highlight the difficulties of establishing relationships between the structure of Mn(II) complexes and the sign of D .…”
Section: Resultsmentioning
confidence: 98%
“…As Mn 2+ with five unpaired 3 d electrons is known to be a T1-shortening agent in MR imaging 42 , MR imaging of H-MnO 2 -PEG/C&D incubated in buffer solutions with different pHs (6 and 7.4) for 6 h was conducted. The significant concentration-dependent brightening effect of H-MnO 2 -PEG/C&D samples were found in T1-MR images at pH 6, whereas the signals of nanoparticles in the neutral buffer solution appeared to be much weaker (Fig.…”
Section: Resultsmentioning
confidence: 99%